A comparative analysis of biopolymer production by microbial and bioelectrochemical technologies. Issue 25 (1st June 2022) - Alvarez Chavez, Brenda; Raghavan, Vijaya; Tartakovsky, Boris
Abstract : Biopolymers production from renewable carbon sources. Abstract : Production of biopolymers from renewable carbon sources provides a path towards a circular economy. This review compares several existing and emerging approaches for polyhydroxyalkanoate (PHA) production from soluble organic and gaseous carbon sources and considers technologies based on pure and mixed microbial cultures. While bioplastics are most often produced from soluble sources of organic carbon, the use of carbon dioxide (CO2 ) as the carbon source for PHA production is emerging as a sustainable approach that combines CO2 sequestration with the production of a value-added product. Techno-economic analysis suggests that the emerging approach of CO2 conversion to carboxylic acids by microbial electrosynthesis followed by microbial PHA production could lead to a novel cost-efficient technology for production of green biopolymers.